Pigeon racing in South Africa: Exploring the socio-economic nature and extent of this 'unknown sport' - Cecilia MOSTERT; Ronnie DONALDSON (GeoSport for Society)
This research addresses the paucity of academic exploration into pigeon racing, a globally recognized sport with limited scholarly attention. While prior studies focused on ornithology and medicine, this paper pioneers a comprehensive examination from a geographical perspective. Employing a quantitative methodology, the study surveyed 712 members of the South African National Pigeon Organization (SANPO), providing a nuanced understanding of demographics, organizational structures, subjective values, and economic impacts within pigeon racing. The study's findings reveal the dominance of males in the sport, its multi-generational nature, and widespread participation across diverse income groups. SANPO, with 3,540 members, emerges as a crucial entity in the sport's landscape. The paper categorizes fanciers into small, medium, and large groups based on bird ownership, presenting insights into their socio-demographic context and motivations. Pigeon-related activities are explored, emphasizing the sport's familial and youth development aspects. The economic analysis highlights the industry's substantial job creation and estimates its total economic worth between R528,968,608 and R1,620,390,112. By shedding light on this understudied sport, the research aims to stimulate further academic exploration and provide a foundation for informed discussions on the cultural, economic, and social aspects of pigeon racing.